Public Sector Accounting, Accountability and Governance Globalising the Experiences of Australia and New Zealand - Pilcher, Robyn; Gilchrist, D. (Routledge, 2018)
? Based on rigorous research by top public sector researchers, this edited collection explores how the concepts of accountability, governance and auditing are applied in practice, providing a unique perspective on the global challenges of ...